Effects of Pseudomonas fluorescens and sulfur on nutrients uptake, growth and yield of groundnut in an alkaline soil - Pratiwi, H; Aini, N; Soelistyono, R (Journal of Degraded and Mining Lands Management, 2016)
The aim of this research was to study the influence of P. fluorescens and sulfur on nutrients uptake, growth and yield of groundnut in alkaline soil. The experiment was conducted in the greenhouse in Malang from January 2015 to Mei 2015. The experiment was laid out in factorial randomized block design consisted of two treatment factors and three replications. The first factor were concentration of P. fluorescens (0 cfu/mL; 107 cfu/mL; and 109 cfu/mL). The second factor were elemental sulfur doses (0 g/kg soil; 1 g/kg soil; 2 /kg soil; and 3 g/kg soil). Soil used was collected from Lamongan East Java, Indonesia. Soil previously was given 40 g Ca(OH)2 /kg soil to achieve pH >8. There was no interaction between P. fluorescens and sulfur on all of parameters observed. P. fluorescens concentration of 109 cfu/mL independently significantly increased availabe Fe in soil as 34.75% compared with the control and could maintain the populations of P. fluorescens better than the concentrations of 0 and 107 cfu/mL. Sulfur significantly correlated with decrease in soil pH expressed by equation y = -0,226x + 8.218. Sulfur independently significantly increased N, P, S, Ca and Mn uptake by plants. Sulfur dose of 3 g/kg of soil provided leaves and stems growth better, increased 80.74% of pod yield and 34.09% of harvest index compared to control.